'So isolation comes in, discrimination and you find many people dying quietly without any family support': Accessing palliative care for key populations – an in-depth qualitative study. (June 2019) - Hunt, Jenny; Bristowe, Katherine; Chidyamatare, Sybille; Harding, Richard
Background: Ensuring palliative care for all under a new global health policy must include key populations, that is, lesbian, gay, bisexual, transgender and intersex (LGBTI) people, and sex workers. Accessibility and quality of care have not been investigated in lower and middle-income countries where civil rights are the weakest. Aim: To examine the accessibility to, and experiences of, palliative care for key populations in Zimbabwe. Design: Qualitative study using thematic analysis of in-depth interviews and focus groups. Setting/participants: A total of 60 key population adults and 12 healthcare providers and representatives of palliative care and key population support organisations were interviewed in four sites (Harare, Bulawayo, Mutare and Masvingo/Beitbridge). Results: Participants described unmet needs and barriers to accessing even basic elements of palliative care. Discrimination by healthcare providers was common, exacerbated by the politico-legal-economic environment. Two dominant themes emerged: (a) minimal understanding of, and negligible access to, palliative care significantly increased the risk of painful, undignified deaths and (b) discriminatory beliefs and practices from healthcare providers, family members and the community negatively affected those living with life-limiting illness, and their wishes at the end of life. Enacted stigma from healthcare providers was a potent obstacle to quality care. Conclusion: Discrimination from healthcare providers and lack of referrals to palliative care services increase the risk of morbidity, mortality and transmission of infectious diseases. Untreated conditions, exclusion from services, and minimal family and social support create unnecessary suffering. Public health programmes addressing other sexually taboo subjects may provide guidance.